Enhanced weathering of olivine in seawater: The efficiency as revealed by thermodynamic scenario analysis: - Griffioen, J. (Elsevier B.V., 2017)
Enhanced weathering of olivine has been suggested as a measure to lower the atmospheric CO2 level and it might also mitigate ocean acidification. This study aimed to characterise how olivine can weather in seawater, to elucidate the role of secondary precipitation and to ascertain the efficiency in terms of molar CO2 removal per mole of olivine dissolution. Geochemical thermodynamic equilibrium modelling was used, which considered both the variable mineralogical composition of olivine and the kinds of secondary precipitates that may be formed. The advantage is that such an approach is independent from local or regional factors as temperature, related kinetics, mineralogy, etc. The results show that the efficiency falls when secondary precipitates are formed. When Fe-bearing olivine undergoes weathering in an oxic environment, Fe(III) hydroxides will inevitably be formed, and as a result of this acidifying process, CO2 could be released to the atmosphere. This might also enhance ocean acidification when Fe-rich olivine becomes used. Ocean alkalinisation only happens when more than 1 mol/kgH2O Mg-rich olivine weathers. Maintenance of supersaturation for calcite or aragonite as holds in seawater reduces the efficiency by about a factor of two compared to the efficiency without secondary precipitation. Precipitation of sepiolite as Mg silicate reduces the efficiency even more. Magnesite precipitation has a similar effect to Ca carbonate precipitation, but according to the literature magnesite precipitation is improbable at ambient conditions and relatively low supersaturation. When less than 0.05 mmol olivine/kg(seawater) weathers the efficiency is slightly different than at higher intensities, due to strong buffering by seawater alkalinity. © 2016 The Author